Patient preferences on general health and colorectal cancer screening decision-making: Results from a national survey. Issue 4 (April 2022) - Zhu, Xuan; Weiser, Emily; Jacobson, Debra J.; Griffin, Joan M.; Limburg, Paul J.; Finney Rutten, Lila J.
Highlights: Patients showed strong desire for involvement in general medical decision-making. Patients preferred collaborative decision-making for colorectal cancer screening. Variations existed across patient subgroups regarding preferred level of control. Abstract: Objective: We examined patient preferences regarding colorectal cancer (CRC) screening decision-making and factors associated with these preferences among screening-eligible US adults. Methods: Through a national survey of 1595 US adults ages 40–75 (response rate: 31.3%), we measured general medical decision-making and CRC screening decision-making preferences (0–100, 100 = highest desire for involvement) and preferred control level over three CRC screening decisions (whether to screen, what method to use, and when to screen). Analyses focused on respondents aged 45–75 at average CRC risk (N = 1062). Results: Respondents expressed strong desire for involvement in general medical decision-making and CRC screening decision-making (Mean = 68.1, 64.4). Over half of respondents reported preferring having equal control as their providers over whether to screen, what method to use, and when to screen. Women and people with higher education expressed higher desire for involvement in general medical decision-making. For CRC screening decision-making, variations exist in preferred level of involvement and control by race/ethnicity, educational attainment, insurance status, and recency of routine checkup. Conclusion: Most respondents preferred a collaborative process of CRC screening decision-making, while variations existed across subgroups. Practice implications: Providers should assess patients' values and preferences and involve them in CRC screening decision-making at a level they are comfortable with.